Training characteristics, performance, and body composition of three U23 elite female triathletes throughout a season - Sellés-Pérez, S.; Arévalo-Chico, H.; Fernández-Sáez, J.; Cejuela, R. (Sports, 2024)
(1) Background: There is a lack of data on the long-term training characteristics and performance markers of elite young female endurance athletes. The aim of this study was to present the training load (ECOs), as well as the evolution of the anthropometric values and performance of three elite U23 female triathletes over a season.